Work Engagement dan Grit sebagai Faktor Penentu Task Performance Karyawan di Midtown Hotel Samarinda - Jahara Salina; Robiansyah Robiansyah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Work engagement and grit are psychological factors that can influence employees’ task performance in carrying out their work. Work engagement describes employees’ involvement in their work, which is characterized by enthusiasm, dedication, and concentration on the tasks being performed. Meanwhile, grit is related to an individual’s perseverance and consistency in maintaining efforts to achieve long-term goals. These two factors are considered to play a role in supporting employees’ ability to complete the tasks that are their responsibilities. This study aims to determine the effect of work engagement and grit on the task performance of employees at Midtown Hotel Samarinda. The method used in this research is a quantitative method with a survey approach. The population in this study consisted of 129 employees, with a sample of 56 respondents determined using the Slovin formula and stratified random sampling technique. Data collection was carried out through the distribution of questionnaires to employees. The data obtained were then analyzed using linear regression analysis with the help of the IBM Statistics 22 application. The results of the study indicate that work engagement does not have a significant effect on task performance with a significance value of 0.304 (>0.05). Meanwhile, grit shows a positive and significant effect on task performance with a significance value of 0.011 (<0.05). Based on these findings, it can be concluded that employees’ perseverance and consistency, which are reflected in grit, have an important role in improving the task performance of employees at Midtown Hotel Samarinda.